Women and violets in France (1800-1920) – a visual journey - Carvalho, Luis; Fernandes, Francisca Maria; Nozes, Paula; Figueira, Ana Paula; a, Sara; Nunes, Maria de Fátima (Ethnobotany Research and Applications, 2023)
Violets were an important trade plant, sold in the streets and markets of European and North America cities throughout the nineteenth century up to the 1920’s, when they began to be out of fashion. France was a major producer of violets and many activities associated with them, such as picking and selling, were commonly done by women. Here we present a selection of photos from Beja Botanical Museum’s collection that represents cultural interactions between women and violets during the nineteenth and early twentieth centuries.